1999
DOI: 10.1523/jneurosci.19-17-07603.1999
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Modulation of Tactile Responses in the Rat Somatosensory System

Abstract: We investigated the influence of four different behavioral states on tactile responses recorded simultaneously via arrays of microwires chronically implanted in the vibrissal representations of the rat ventral posterior medial nucleus (VPM) of the thalamus and the primary somatosensory cortex (SI). Brief (100 microsecond) electrical stimuli delivered via a cuff electrode to the infraorbital nerve yielded robust sensory responses in VPM and SI during states of quiet immobility. However, significant reductions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
266
3
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 314 publications
(298 citation statements)
references
References 38 publications
25
266
3
4
Order By: Relevance
“…Changes in coherence between unit activity in motor cortex, as opposed to sensory cortex in the present work, and the underlying tremor in motoneuron output have been observed for hand muscles in monkey during a precision grip task (33,34). Although the underlying mechanism for either effect is unknown, modulators of cortical excitability could increase the extent of phase-locking, perhaps controlled by thalamic-induced gain control (35) or synchrony across cortex (36,37). Past studies have shown that attention can regulate the timing or synchrony of neuronal responses in sensory cortex, as opposed to the rate of spiking.…”
Section: Discussionsupporting
confidence: 47%
“…Changes in coherence between unit activity in motor cortex, as opposed to sensory cortex in the present work, and the underlying tremor in motoneuron output have been observed for hand muscles in monkey during a precision grip task (33,34). Although the underlying mechanism for either effect is unknown, modulators of cortical excitability could increase the extent of phase-locking, perhaps controlled by thalamic-induced gain control (35) or synchrony across cortex (36,37). Past studies have shown that attention can regulate the timing or synchrony of neuronal responses in sensory cortex, as opposed to the rate of spiking.…”
Section: Discussionsupporting
confidence: 47%
“…Interestingly however, during these active states, the frequency-dependent depression was almost abolished (Fanselow & Nicolelis, 1999). This suggests that the somatosensory system is able to modulate the effectiveness of tactile information in o~der to optimize the transfer of information depending upon the behavioral state ofthe animal.…”
Section: • •mentioning
confidence: 96%
“…Short-term plasticity of thalamocortical pathways can he dynamically modulated with behavioral state (Castro-Alamancos " Connors, 1996a;Fanselow & Nicolelis, 1999). For example, stimulating the ventrolateral nucleus of the thalamus at frequencies ranging from 7-14 Hz causes an enhanced response for each successive stimulus, relative to the tirst (Castro-Alamancos &- Connors, 1996a,-b, cl.…”
Section: Modulation Ofshort-term Plasticilymentioning
confidence: 99%
“…Neurons of the whisker barrel system in the rodent primary somatosensory cortex are known to encode external events in time and space and thus offer an excellent model to study BOLD activation processes (de Celis Alonso et al, 2012;Lu et al, 2003;Yang et al, 1996Yang et al, , 1997. The rat barrel cortex can also be reliably and reproducibly activated through trigeminal nerve (TGN) stimulation (Nielsen and Lauritzen, 2001;Just et al, 2010;Fanselow and Nicolelis, 1999). BOLD responses to short TGN stimulations (30 s) were characterized as a function of stimulus frequency and current intensity (Just et al, 2010) showing robust and reproducible BOLD activation of the primary somatosensory barrel field cortex (S1BF).…”
Section: Introductionmentioning
confidence: 99%